EFEKTIVITAS LAYANAN INFORMASI DENGAN MEDIA FILM PENDEK DALAM MENINGKATKAN PEMAHAMAN TENTANG DAMPAK BULLYING DI SMAN 1 MUARO JAMBI - sanuryanti sitompul; Rasimin Rasimin; Ferdiansyah Ferdiansyah (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2024)
This research aims to find out whether information services with short film media can improve understanding of the impact of bullying in SMAN 1 Muaro Jambi. This research is a type of quantitative research using experimental research methods and pre- experimental variations one group pretest-posttest. The population in this study is the entire student XI SMAN 1 Muaro Jambi. As for sampling in this study using purposive samplings based on specific characteristics, samples of 36 people were obtained. (satu kelompok eksperimen). The data collection tool in this study uses a questionnaire or an understanding test with a total of 35 items. The data analysis techniques used are percentage tests and t-tests. The results of this study show that information services with short film media can improve understanding of the impact of bullying in SMAN 1 Muaro Jambi with the result of pretest before given treatment or treatment of 652 and after given treatment (posttest) of 1811.Based on the results of T-test calculations using SPSS 23.0 using the calculation of degree of freedom 40 of 2.03011 which means there is a signative influence between the information service with improved understanding of Bullying before and after giving treatment/treatment.